2016
DOI: 10.1177/1473325016680285
|View full text |Cite
|
Sign up to set email alerts
|

Professional relationships and decision making in social work: Lessons from a Scottish case study of secure accommodation decision making

Abstract: There has been a great deal written in recent years about the complexities of social work decision making in the minority world and the need for a more ecological conceptualisation of the decision making task in child welfare and protection. This article outlines some of the findings from a PhD study of secure accommodation decision making in Scotland which sought to understand the dynamics of local social work decision making in cases where children and young people pose a significant risk to themselves and/o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…For example, a study by Nouwen et al (2012) suggested conceptualizing the decision-making process in child welfare services as a group practice and iterative process based on reflexivity and shared information. The importance of colleague interactions, and more specifically, reciprocity, exchange, and confidence between child welfare professionals in the decision-making process are also mentioned in a recent study by Roesch-Marsh (2018). Social workers questioned in the present study mention the collective and consultative aspects of the decisions concerning the child's removal as well as the choice of foster care environment: In both cases, they speak of the existence of procedures based on exchange, consultation, and teamwork.…”
Section: Discussionmentioning
confidence: 55%
“…For example, a study by Nouwen et al (2012) suggested conceptualizing the decision-making process in child welfare services as a group practice and iterative process based on reflexivity and shared information. The importance of colleague interactions, and more specifically, reciprocity, exchange, and confidence between child welfare professionals in the decision-making process are also mentioned in a recent study by Roesch-Marsh (2018). Social workers questioned in the present study mention the collective and consultative aspects of the decisions concerning the child's removal as well as the choice of foster care environment: In both cases, they speak of the existence of procedures based on exchange, consultation, and teamwork.…”
Section: Discussionmentioning
confidence: 55%
“…The way a case is framed in initial conversations with colleagues offers insight into the way the case is beginning to be formulated by the social worker (Helm, 2013). Social work colleagues then act as a sounding board for exploring different conceptualisations of a case (Helm, 2017), whilst supervisors, colleagues and other professionals offer opportunities for further sensemaking and narrative-building (Biggart et al, 2017;Roesch-Marsh, 2018). This enables a judgement to be reached in the process of completing an assessment: a story is built via a sensemaking process until it has coherence and can inform action.…”
Section: Sensemaking As Social Storytellingmentioning
confidence: 99%
“…Weick et al (2005) highlight that social systems interact with, and influence, the sensemaking process. Sensemaking is influenced by wider, dominant narratives about childhood and social work Collings and Davies, 2008;Parton, 2011) as well as the team an organisational environments in which sensemaking takes place (Helm, 2017;Roesch-Marsh, 2018).…”
mentioning
confidence: 99%
See 1 more Smart Citation